CD38 expression on gluten‐specific T cells is a robust marker of gluten re‐exposure in coeliac disease. Issue 10 (1st December 2019) - Zühlke, Stephanie; Risnes, Louise Fremgaard; Dahal-Koirala, Shiva; Christophersen, Asbjørn; Sollid, Ludvig M; Lundin, Knut EA
Abstract : Background: Increasing efforts are being put into new treatment options for coeliac disease (CeD), a chronic disorder of the small intestine induced by gluten. Interleukin‐2 (IL‐2) and gluten‐specific CD4 + T cells increase in the blood after four hours and six days, respectively, following a gluten challenge in CeD patients. These responses are unique to CeD and are not seen in controls. We aimed to evaluate different markers reflecting a recall response to gluten exposure that may be used to monitor therapy. Methods: CeD patients on a gluten‐free diet underwent a one‐ ( n  = 6) or three‐day ( n  = 7) oral gluten challenges. We collected blood samples at several time points between baseline and day 8, and monitored gluten‐specific CD4 + T cells for their frequency and CD38 expression using HLA‐DQ:gluten tetramers. We assessed the IL‐2 concentration in plasma four hours after the first gluten intake. Results: The frequency of gut‐homing, tetramer‐binding, CD4 + effector memory T (tetramer + β7 + TEM ) cells and the IL‐2 concentration measured shortly after the first dose of gluten increased significantly after the one‐ and three‐day gluten challenges, but large interindividual differences were exhibited. The frequency of tetramer + β7 + TEM plateaued between days 6 and 8 and was lower after the one‐day challenge. We observed a consistent increase in CD38 expression on tetramer + β7 + TEM cells and did not find a significant difference between the one‐ and three‐day challenges. Conclusions: The optimal time points for monitoring therapy response in CeD after a three‐day oral gluten challenge is four hours for plasma IL‐2 or six to eight days for the frequency of tetramer + β7 + TEM cells, but both these parameters involved large interindividual differences. In contrast, CD38 expression on tetramer + β7 + TEM cells increased uniformly and irrespectively of the length of gluten challenge, suggesting that this parameter is more suited for monitoring drug efficacy in clinical trials for CeD.